Training for diversity - Smith, Bryan (Management consultant); Bagshaw, Mike (Industrial and commercial training, 2004)
This article provides human resource professionals and managers with an insight into the under representation of women/ethnic minorities at senior management level in UK organisations and the issues involved in increasing diversity in leadership. It describes three leadership studies carried out by Pearn Kandola covering: barriers to the career progress of ethnic minorities; differences in perception of male and female managerial success; and changing leadership behaviour. The research was conducted via literature reviews and interviews with HR/diversity specialists, senior managers and ethnic.